Colon Sparing Endoscopic Full-Thickness Resection for Advanced Colorectal Lesions: Is It Time for Global Adoption? - Wu, Zhong-Wei; Ding, Chao-Hui; Song, Yao-Dong; Cui, Zong-Chao; Bi, Xiu-Qian; Cheng, Bo (Frontiers in Oncology, 2022)
The majority of colon lesions are <10 mm in size and are easily resected by endoscopists with appropriate basic training. Lesions ≥10 mm in size are difficult to remove technically, and are associated with higher rates of incomplete resection. Currently, the main endoscopic approaches include endoscopic mucosal resection (EMR) for lesions without submucosal invasion, and endoscopic submucosal dissection (ESD) for relatively larger lesions involving the superficial submucosal layer. Both of these approaches have limitations, EMR cannot reliably ensure complete resection for larger tumors and recurrence is a key limitation. ESD reliably provides complete resection and an accurate pathological diagnosis but is associated with risk such as perforation or bleeding. In addition, both EMR and ESD may be ineffective in treating subepithelial lesions that extend beyond the submucosa. Endoscopic full-thickness resection (EFTR) is an emerging innovative endoscopic therapy which was developed to overcome the limitations of EMR and ESD. Advantages include enabling a transmural resection, complete resection of complex colorectal lesions involving the mucosa to the muscularis propria. Recent studies comparing EFTR with current resection techniques and radical surgery for relatively complicated and larger lesion have provided promising results. If the current trajectory of research and development is maintained, EFTR will likely to become a strong contender as an alternative standard of care for advanced colonic lesions. In the current study we aimed to address this need, and highlighted the areas of future research, while stressing the need for multinational collaboration provide the steppingstone(s) needed to bring EFTR to the mainstream.